KOREOGRAFI TARI NELAYAN DI SANGGAR ATOK RUMBIO KENAGARIAN JINANG KAMPUNG PANSUR KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Melisa, Septia; Rosalina, Venny (Universitas Negeri Padang, 2026)
This study aims to describe and analyze the choreography of the Fisherman's Dance at the Atok Rumbio Studio, Jinang Village, Pansur Village, Koto XI Tarusan District, Pesisir Selatan Regency. The Fisherman's Dance is a creative dance work that explores the livelihood activities of coastal communities in the area. This research is qualitative and uses descriptive methods. Data collection techniques were conducted through observation, interviews, and documentation studies. The research instrument was the researcher himself, with the assistance of supporting tools such as writing utensils and a camera. Data analysis techniques included data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Fisherman's Dance choreography comprises two aspects: process and form. Based on the process, the choreographer began the choreographic process for this dance, which includes theme/idea, improvisation, exploration, and composition. In terms of form, the choreographer creates various elements, including dancers, movements, floor design, group composition, props, makeup and costumes, and accompanying music. This dance is a creative movement. The Fisherman's Dance consists of 18 movements: the Opening Movement, the Front Pasambahan Movement, the Ambiak Step Movement, the First Step Movement, the Gelek Movement, the Pull Back Step Movement, the Three Step Movement, the Forward Step Movement, the Maayun Tuduang Movement, the Pisawek Gantuang Movement, the Hanged Step Movement, the Mereng Movement, the Ampun Movement, the Maagiah Umpan Movement, the Manjapuik Bait Right Movement, the Manjapuik Bait Left Movement, the Mandorong Umpan Movement, and the Ending Movement. The dance accompaniment used in the Fisherman's Dance includes the chanting, gandang, bansi, talempong, and string instruments. The costumes used are modified to allow the dancers to move easily. These include clothing made of satin, sarawa, songket, batik, and tassels, with talepon earrings and a cakik necklace. The prop used in the Fisherman's Dance is a hat.